Safeguarding the Integrity of Science Communication by Restraining 'Rational Cheating' in Peer Review - Barroga, Edward F. (Journal of Korean Medical Science, 2014)
Peer review is the pillar of the integrity of science communication. It is often beset with flaws as well as accusations of unreliability and lack of predictive validity. 'Rational cheating' by reviewers is a threat to the validity of peer review. It may diminish the value of good papers by unfavourable appraisals of the reviewers whose own works have lower scientific merits. This article analyzes the mechanics and defects of peer review and focuses on rational cheating in peer review, its implications, and options to restrain it.